Economic gains from migration to the urban western frontier in the United States, 1900–1910: A longitudinal analysis. Issue 3 (2nd July 2016) - Tiagi, Raaj
ABSTRACT: During the early twentieth century, cities along the Pacific coast constituted the new urban frontier. This article examines whether internal migrants gained economically by moving to this new urban frontier, relative to an option of not migrating, or an option of migrating to the established cities in the Midwest and the Northeast. For the analysis, a longitudinal data set was constructed by linking individuals from the 1910 IPUMS sample to the 1900 Census through the genealogy website, Ancestry.com . Results suggest that compared to an option of not migrating, there were significant economic gains to migrating to the urban western frontier. However, migrants to the Midwest and the Northeast gained about the same, economically, as migrants to the urban western frontier.